Race, pigmentation, and the human skin barrier—considerations for dermal absorption studies - Salminen, Alec T.; Manga, Prashiela; Camacho, Luísa (Frontiers in Toxicology, 2023)
A functional human skin barrier is critical in limiting harmful exposure to environmental agents and regulating the absorption of intentionally applied topical drug and cosmetic products. Inherent differences in the skin barrier between consumers due to extrinsic and intrinsic factors are an important consideration in the safety assessment of dermatological products. Race is a concept often used to describe a group of people who share distinct physical characteristics. The observed predisposition of specific racial groups to certain skin pathologies highlights the potential differences in skin physiology between these groups. In the context of the human skin barrier, however, the current data correlating function to race often conflict, likely as a consequence of the range of experimental approaches and controls used in the existing works. To date, a variety of methods have been developed for evaluating compound permeation through the human skin, both in vivo and in vitro. Additionally, great strides have been made in the development of reconstructed human pigmented skin models, with the flexibility to incorporate melanocytes from donors of different race and pigmentation levels. Together, the advances in the production of reconstructed human skin models and the increased adoption of in vitro methodologies show potential to aid in the standardization of dermal absorption studies for discerning racial- and skin pigmentation-dependent differences in the human skin barrier. This review analyzes the existing data on skin permeation, focusing on its interaction with race and skin pigmentation, and highlights the tools and research opportunities to better represent the diversity of the human populations in dermal absorption assessments.